You'll never walk alone: Why we need a supply chain practice view on digital procurement. Issue 4 (October 2019) - Kosmol, Tobias; Reimann, Felix; Kaufmann, Lutz
Abstract: This paper conceptualizes digital procurement readiness as a dyadic construct and introduces the supply chain practice view (SCPV) as a theoretical lens that can help guide future research on digital procurement. We build on a literature review and on dyadic, explanatory case studies to provide a nuanced understanding of how the digital readiness of supply chain partners—on both sides of the dyad—needs to co-evolve for the implementation of digital procurement practices. Specifically, we outline how the SCPV can serve as both a holistic and a supply chain-specific framework for future research on the following: 1) the antecedents that help explain why supply chain partners adopt inter-organizational digital procurement practices, and 2) the relational performance outcomes derived from their use. For managers, this study implies the need to explicitly consider interactions with and influences of supply chain partners in their quest to rapidly and effectively digitalize procurement. Highlights: Conceptualizes digital procurement readiness as a dyadic construct. Introduces the supply chain practice view (SCPV) on digital procurement. Demonstrates the applicability of the SCPV to salient supply chain phenomena. Highlights the role of co-evolution between buyer and supplier.